Many-Ended Complete Minimal Surfaces Between Two Parallel Planes in â„³ - Brito, Francisco (CUBO, A Mathematical Journal, 2008)
We use some special convergent Hadamard gap series to provide examples of complete minimal surfaces of many different conformal types between two parallel planes in three dimensional Euclidean space.